NILAI- NILAI KEISLAMAN DALAM PELESTARIAN BUDAYA LOKAL PENCAK MACAN DI DESA LUMPUR GRESIK - Nur Khamim; Moh Syamsi (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2022)
In the mud village there are several local traditions and cultures that are preserved until now including Pencak Macan, Bandungan, and Macapat Sindujoyo. This research was conducted to find out how Islamic values are contained in the preservation of local culture in Lumpur Gresik Village and how to implement its preservation. For data collection, the authors used several methods including observation, interviews, and documentation. Based on the descriptions that the author has explained to the collected research data, which are then processed, the author gets the following conclusion: In Lumpur Village, there are many local cultures and diverse traditions, and some of them are researched by researchers, including Pencak Macan. In the implementation of this tradition, it contains many philosophical meanings and pitutur messages to the Mud community in particular. Not only philosophical meanings as well, but in local culture there are many Islamic values that exist in it, including remembering history, patience, tawakkal, and gratitude to Allah SWT.